2006
DOI: 10.1136/gut.2005.070342
|View full text |Cite
|
Sign up to set email alerts
|

Iron loading and morbidity among relatives of HFE C282Y homozygotes identified either by population genetic testing or presenting as patients

Abstract: Background and aims: Although most cases of hereditary haemochromatosis are associated with homozygosity for the C282Y mutation of the HFE gene, clinical penetrance varies and other genes may modify disease expression. If so, relatives from clinically affected families, by inheriting such genes, may accumulate more iron. To seek evidence for this, we compared iron status and morbidity in unselected first degree relatives of two groups of index cases from South Wales, namely asymptomatic C282Y homozygotes ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 50 publications
5
38
4
Order By: Relevance
“…In contrast, participants in the large multicentre HEIRS Study were enrolled without regard to any clinical conditions. Our findings are consistent with the results of several single-centre and regional population-and primary care-based studies (15)(16)(17)(18). A recent study of first-degree relatives of patients with known C282Y hemochromatosis also found a low prevalence of clinical manifestations in family members who were C282Y homozygotes or C282Y/H63D compound heterozygotes, despite evidence of iron overload in most cases (31).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In contrast, participants in the large multicentre HEIRS Study were enrolled without regard to any clinical conditions. Our findings are consistent with the results of several single-centre and regional population-and primary care-based studies (15)(16)(17)(18). A recent study of first-degree relatives of patients with known C282Y hemochromatosis also found a low prevalence of clinical manifestations in family members who were C282Y homozygotes or C282Y/H63D compound heterozygotes, despite evidence of iron overload in most cases (31).…”
Section: Discussionsupporting
confidence: 81%
“…By self-identified race/ethnicity, 44% of the participants were non-Hispanic Caucasians. As previously reported (24), the frequency of homozygosity for the C282Y mutation in this group of non-Hispanic Caucasians was 4.4 per 1000 subjects; consistent with the findings of other screening studies (9,18,(25)(26)(27)(28)(29) had SF below these levels. Eighty-seven other participants with C282Y homozygosity reported they previously were told by a physician that they had hemochromatosis or iron overload, or had been treated by therapeutic phlebotomy, including 39 (45%) women and 48 (55%) men, of median age 56 years (range 25 to 83 years).…”
Section: Study Populationsupporting
confidence: 78%
See 2 more Smart Citations
“…Mere HFE hetero-or homozygosity may therefore not be a sufficient marker of perturbated iron distribution. In fact, siblings and twins of probands with phenotypic haemochromatosis are known to have higher levels of iron compared with those related to probands with a haemochromatosis genotype, but not phenotype [17,18], suggesting that other factors are critical for the expression of phenotypic disease. Thus, in the context of a family history of genetic haemochromatosis (GH), the observed risks of IHD among individuals heterozygous for HFE mutations may be different from those for individuals with HFE mutations detected through population screening, but the risks of IHD in the former remain unclear [19][20][21].…”
Section: Introductionmentioning
confidence: 99%